Epigenetic and senescence markers indicate an accelerated ageing-like state in women with preeclamptic pregnancies - Suvakov, Sonja; Ghamrawi, Ranine; Cubro, Hajrunisa; Tu, Haitao; White, Wendy M.; Tobah, Yvonne S. Butler; Milic, Natasa M.; Grande, Joseph P.; Cunningham, Julie M.; Chebib, Fouad T.; Prata, Larissa G.P. Langhi; Zhu, Yi; et al. (EBioMedicine, 2021)
Preeclampsia is a pregnancy-specific hypertensive disorder characterized by proteinuria and/or multisystem involvement. Disease-specific therapy has yet to be developed due to the lack of understanding of underlying mechanism(s). We postulate that accelerated ageing in general, and particularly cellular senescence, play a role in its pathophysiology. We compared women with preeclampsia vs. normotensive pregnancies with respect to epigenetic markers of ageing and markers of senescence in tissues/organs affected by preeclampsia (blood, urine, adipose tissue, and kidney). We demonstrate that preeclamptic compared to normotensive pregnant women: (i) undergo accelerated epigenetic ageing during pregnancy, as demonstrated by an “epigenetic clock”; (ii) exhibit higher levels/expression of senescence-associated secretory phenotype factors in blood and adipose tissue; (iii) display increased expression of p16INK4A in adipose tissue and renal sections, and (iv) demonstrate decreased levels of urinary α-Klotho (an anti-ageing protein) at the time of delivery. Finally, we provide data indicating that pre-treatment with dasatinib, a senolytic agent, rescues the angiogenic potential of mesenchymal stem cells (MSC) obtained from preeclamptic pregnancies, and promotes angiogenesis, even under pro-inflammatory conditions. Taken together, our results identify senescence as one of the mechanisms underpinning the pathophysiology of preeclampsia. Therapeutic strategies that target senescent cells may offer novel mechanism-based treatments for preeclampsia. This work was supported by NIH grants, R01 HL136348, R37 AG013925, P01 AG062413, R01 DK11916, generous gifts from the Connor Fund, Robert J. and Theresa W. Ryan and from The George G. Beasley family, the Noaber Foundation, and the Henry and Emma Meyer Professorship in Molecular Genetics.